Phylogenetic relationships of Eurema butterflies from Peninsular Malaysia inferred from COI and 28S gene sequences with emphasis on Eurema hecabe - Abdul Wahid, Noor Azrizal; Idid, Mohammed Rizman; Azirun, Mohd Sofian (Raffles Museum of Biodiversity Research, 2021)
The phylogenetic relationships among species of the genus Eurema from Peninsular Malaysia were reconstructed using nucleotide sequences of mitochondrial CO1 (307 bp) and nuclear ribosomal 28S DNA (471 bp). A total of twenty-eight sequences generated through PCR amplification for each gene region were used to construct the Maximum Likelihood (ML) and Maximum Parsimony (MP) phylogenetic trees. The separate taxonomic grouping of the genus Eurema and the genus Gandaca, and their close association is tested here together with sequences of other pierid butterflies obtained from GenBank. All trees reveal a strongly supported monophyletic group of Eurema conspecifics and well-resolved interspecific genetic distances, indicating the usefulness of the genetic markers in local species identification. The combined phylogenetic analyses of CO1 and 28S genes strongly supports a close relationship of E. hecabe with E. blanda, while E. andersonii is recovered as a sister taxon to E. ada.